Phase II study of gemcitabine and cisplatin as first-line chemotherapy in inoperable biliary tract carcinoma - Thongprasert S. (2014)
Objectives: The prognosis for patients with unresectable biliary tract cancer is poor and existing chemotherapy is relatively ineffective. Therefore, a need exists for new, effective chemotherapeutic regimens. The aim of this study was to determine the efficacy and safety profile of gemcitabine plus cisplatin in patients with unresectable biliary tract cancer (cholangiocarcinoma) and gall bladder cancer. Methods: From December 2000 to July 2002, 43 patients received gemcitabine 1250mg/m2 in a 30-min i.v. infusion on d1, 8 and cisplatin 75 mg/m2 in a 2-h i.v. infusion on d1 (with appropriate hydration), every 3 weeks. Eligibility: Normal hematologic parameters and creatinine levels; serum bilirubin <5 mg/dl. Results: Forty-three patients enrolled; 40 were assessable (three patients were not assessable due to incomplete treatment; they chose to discontinue chemotherapy after the first cycle). There were 23 males and 17 females, median age 50 years (range 31-69), median Karnofsky PS 80%. Tumor types: cholangiocarcinoma (39), gall bladder cancer (1). Median number of chemotherapy courses was four (range 1-8). Overall response rate was 27.5% (PR in 11 pts), with 32.5% SD and/or minor response. Median survival time was 36 weeks. Grade 3 hematologic toxicity: anemia (4.33%), leukopenia (1.73%). Non-hematologic toxicity (i.e. rash, nausea, vomiting, neuropathy and myalgia) ranged from mild to moderate. Conclusions: Gemcitabine plus cisplatin is active in biliary tract carcinoma. These data warrant further investigation of single-agent gemcitabine versus gemcitabine plus cisplatin or its derivative, i.e. oxaliplatin. © 2005 European Society for Medical Oncology.